2010
DOI: 10.6009/jjrt.66.371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 99mTc-myocardial Perfusion SPECT Attenuation Correction by Hybrid SPECT/CT-Examination by Quantitative Analysis-

Abstract: A non-uniform attenuation correction is necessary for the myocardial perfusion image (MPI) SPECT that is one of the images of the trunk. Simultaneous non-uniform attenuation correction during the process of SPECT reconstruction was enabled by developing hybrid SPECT/CT. Image acquisition of 99m Tc MPI with hybrid SPECT/CT was performed in a phantom study and clinical cases We evaluated the effect of non-uniform attenuation correction by Filtered Back Projection (FBP) or Ordered Subsets-Expectation Maximization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Attenuation correction, however, induces an artifactual myocardial perfusion defect at the apex, which is called "apical thinning" [11][12][13][14]. Subsequently, this phenomenon induces falsepositive hypoperfusion in normal perfusion and reduces specificity for the detection of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation correction, however, induces an artifactual myocardial perfusion defect at the apex, which is called "apical thinning" [11][12][13][14]. Subsequently, this phenomenon induces falsepositive hypoperfusion in normal perfusion and reduces specificity for the detection of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a phantom study on conventional SPECT with a parallel-hole collimator has shown that CTAC can introduce artificial apical defects [15]. Furthermore, in a study in human using technetium-99m tetrofosmin MPS with a parallel-hole collimator, myocardial tracer accumulation in the apex was lower in supine images acquired with CTAC than in those acquired without CTAC [16].…”
Section: Discussionmentioning
confidence: 98%